The Gayo Kerawang Motifs at the Keni Gayo Statue in Central Aceh Regency - Maulidha SA; Ikhwanuddin Nasution; Agus Priyatno; Lenna Shaness (Universitas Negeri Medan, 2025)
This study aims to systematically describe the names, patterns, and motifs of kerawang Gayo applied to the keni Gayo Statue in Central Aceh Regency, as well as to explain the contribution of this statue to cultural preservation and the strengthening of Gayo community identity. This study uses a qualitative descriptive method, data sources were obtained through observation, documentation and interviews with seventeen informants, in addition, data were also obtained through libraries, theories and other literature. The data obtained were summarized, described between categories and concluded. There are six main motifs applied to the Gayo keni statue, such as emun berangkat, saraq opat, tali mestike, pucuk rebung, bunge lawang, and emun beriring. Each motif is applied in a structured manner, adhering to the aesthetic principles and cultural values of the Gayo people.The research findings reveal that the keni Gayo statue serves not only as an aesthetic element in public space but also as an effective medium for cultural communication. The statue fosters a sense of identity, strengthens social solidarity, and nurtures collective pride among the community. Through its presence in open spaces, the statue plays a significant role in introducing cultural values to younger generations and reinforcing local cultural narratives amid globalization. A model like the keni Gayo statue can serve as an inspiration for efforts to reinforce national cultural identity through contemporary visual media rooted in local traditions.